Method for reduction of methane production per unit of Volatile Fatty Acids (VFA) production from ruminants and improvement of microbial feed degradation using lactic acid bacteria (LAB). - Liang, Juan Boo; Jahromi, Mohammad Faseleh; Shokryazdan, Parisa (2011)
A method for isolating potential lactic acid bacteria (LAB) which acts as probiotic from a feed capable of reducing ruminal gas production per unit of Volatile Fatty Acids (VFA) in a rumen of a ruminant includes the steps of providing a selective media for selecting lactic acid bacteria (LAB) from the feed, testing the selected lactic acid bacteria (LAB) for multiple test parameters, identifying multiple isolates based on at least one result of the multiple test parameters and isolating at least one strain of lactic acid bacteria (LAB) from the identified multiple isolates by using at least one molecular biology method. The at least one strain of lactic acid bacteria (LAB) isolated is selected from at least two different cultures of bacterial strains.